The Contribution of Early Breastfeeding Initiation (IMD) to Exclusive Breastfeeding and the Relationship with Nutritional Status of Child - Almas Awanis; Lilik Ariyanti (Indonesian Journal of Global Health Research, 2022)
Early initiation of breastfeeding (IMD) is one of the government's policy can reduce the neonatal mortality rate (AKN) and increase the coverage of exclusive breastfeeding. The Failure of IMD and exclusive breastfeeding can be the one of causes for children have poor nutritional status. The purpose of this research is to examine of early initiation of breastfeeding for exclusive breastfeeding and to know the relationship with nutritional status of children. The research sample as many as 130 people by using purposive sampling. This study using quantitative methods, with cross-sectional design. Data collection instruments such as questionnaires, and measuring the children's height and weight. Data Analysis used to find results of contribution about relationship between IMD and exclusive breastfeeding was with chi-square test, and used to find results of correlation with nutritional status was carried with the Pearson Correlation and Lamda tests. The results showed that there was a relationship Early Initiation of Breastfeeding (IMD) (p =0,00) OR (6,7) CI 95%. Analyzed showed that dominant risk factor of early initiation of breastfeeding is early initiation of breastfeeding. And than for the results of IMD with nutritional status showed that (r = 0.00) that's mean it does not have a strong correlation.